On the Practical Stability of Impulsive Differential Equations with Infinite Delay in Terms of Two Measures - Bo Wu; Jing Han; Xiushan Cai (Abstract and Applied Analysis)
We consider the practical stability of impulsive differential equations with infinite delay in terms of two measures. New stability criteria are established by employing Lyapunov functions and Razumikhin technique. Moreover, an example is given to illustrate the advantage of the obtained result.